2010
DOI: 10.1007/s10899-010-9193-1
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitions in Problem Gambling

Abstract: Problem gambling is heterogeneous in nature, ranging in severity from occasional but problematic gambling episodes, to extreme, impulsive and pervasive gambling behaviour. Problem gambling may be accompanied by a sense of impaired control and can give rise to financial, interpersonal, legal and vocational costs for the sufferer, their families and society. This study investigated the relationship among metacognitions, anxiety, depression and gambling in a sample of problem gamblers. A total of 91 individuals a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 30 publications
4
24
0
Order By: Relevance
“…The Metacognitive Theory maintains that nonfunctional beliefs about cognitions, which form the metacognitions, are central to the improvement and maintenance of psychological disorders (Wells, 2000;Wells & Mathews, 1994). For example, these beliefs have also been found to be related to other distress phenomena, for instance, perfectionism (Flett, Hewitt, Blankstein, & Gray, 1998), eating disorders (e.g., Vitousek, 1996), pathological gambling (Lindberg et al, 2011), physical symptoms of illness (Aydin, 1997), suicide-related responses (Nock & Kazdin, 2002), seasonal affective disorder (e.g., Rohan, Sigmon, & Dorhofer, 2003), and generalized anxiety disorder . Moreover, Wells' (2009) metacognitive therapy (MCT) model accentuates the importance of both cognitive and metacognitive dimensions of thinking.…”
Section: Discussionmentioning
confidence: 99%
“…The Metacognitive Theory maintains that nonfunctional beliefs about cognitions, which form the metacognitions, are central to the improvement and maintenance of psychological disorders (Wells, 2000;Wells & Mathews, 1994). For example, these beliefs have also been found to be related to other distress phenomena, for instance, perfectionism (Flett, Hewitt, Blankstein, & Gray, 1998), eating disorders (e.g., Vitousek, 1996), pathological gambling (Lindberg et al, 2011), physical symptoms of illness (Aydin, 1997), suicide-related responses (Nock & Kazdin, 2002), seasonal affective disorder (e.g., Rohan, Sigmon, & Dorhofer, 2003), and generalized anxiety disorder . Moreover, Wells' (2009) metacognitive therapy (MCT) model accentuates the importance of both cognitive and metacognitive dimensions of thinking.…”
Section: Discussionmentioning
confidence: 99%
“…Research has also shown that general negative metacognitive beliefs are elevated across addictive behaviours including alcohol (Spada, Caselli, & Wells, 2009; Wells, 2005;Spada, Zandvoort & Wells, 2007), gambling (Lindberg, Fernie & Spada, 2011), nicotine Spada, Nikčević, Moneta & Wells, 2007) and Internet use (Spada, Langston, Nikčević & Moneta, 2008). These studies have tended to show that negative metacognitive beliefs about the need to control thoughts and lack of cognitive confidence positively predict addictive behavior.…”
Section: Metacognitive Beliefsmentioning
confidence: 99%
“…Although several studies dealt with the independent role of comorbid disorders (Johansson et al 2009;Lorains et al 2011) and metacognition (Lindberg et al 2011) on the onset of pathological gambling, to our knowledge no research has assessed whether the presence of concurrent psychological disorders could have accounted for the associations between metacognition and pathological gambling. Our data showed a higher level of comorbid disorders (especially depression and anxiety disorders) of the pathological gamblers associated with an increase in the severity of gambling.…”
Section: Discussionmentioning
confidence: 99%
“…The mediational model was tested in according to Baron and Kenny's criteria (1986), thus fully or partially mediating relationship occurs when the relationship between the predictor and criterion is non-significant or still significant, respectively, after controlling for the effect of the mediator. Meditational analyses were chosen on the basis of the associations between metacognition and psychological disorders (Wells 2009(Wells , 2012, and between metacognition and gambling (Lindberg et al 2011). The significance of the indirect effect was tested utilizing a bootstrapping procedure, recommended in assessing the mediation models for small size samples (MacKinnon et al 2002;Preacher and Hayes 2004).…”
Section: Statisticsmentioning
confidence: 99%
See 1 more Smart Citation